Consumer perceptions of fruit and vegetable quality: certification and other options for safeguarding public health in West Africa - Keraita, Bernard N.; Drechsel, Pay (International Water Management Institute, 2015)
With increasing change of traditional diets, and the emergence of new supply and marketing chains, urban food consumers in low-income countries are faced with multiple food safety challenges, among which microbial contamination and pesticides are key concerns for fruits and vegetables sold on urban markets in West Africa. Although consumers have a genuine interest in healthy food, and are willing to pay premiums, their interpretation of food quality and risks deviates from scientific health risk assessments and does not translate into recommended risk mitigation behavior. To safeguard public health, alternative measures are needed to support consumers’ risk awareness and decision making. The review looked at common and less-common options to trigger and support behavioral change, including safety labeling (certification), corporate social responsibility models, incentive systems and social marketing of safe practices, to address potential food safety risks from farming in urban and peri-urban areas. Overall, it appears that regulatory measures for risk management, including certifications, will be – for now – less effective in the West African setup due to low educational levels in view of chemical and microbial risk, diverse and often informal food chains, poor safety supporting infrastructure and weak institutional capacities for compliance monitoring.